2022
DOI: 10.7554/elife.68253
|View full text |Cite
|
Sign up to set email alerts
|

A general approach for stabilizing nanobodies for intracellular expression

Abstract: Conventional antibodies and their derived fragments are difficult to deploy against intracellular targets in live cells, due to their bulk and structural complexity. Nanobodies provide an alternative modality, with well-documented examples of intracellular expression. Despite their promise as intracellular reagents, there has not been a systematic study of nanobody intracellular expression. Here, we examined intracellular expression of 75 nanobodies from the Protein Data Bank. Surprisingly, a majority of these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 35 publications
2
35
1
Order By: Relevance
“…As for the TANGO, we compared both β-arrestin-1 and β-arrestin-2 fused at the N- or C-terminus with the V5-tag; the ALFA-tag was also included as a reference because the corresponding NbALFA intrabody is already characterized and was shown to work well with all placements (N-term, C-term, and internal) of the tag. As shown in Fig.4b-d , all configurations produced a robust signal, but C-terminally tagged NbV5 (NbV5-GFP2) gave a better BRET 2 ratio, while the NbALFA is less affected. As shown in Ext.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…As for the TANGO, we compared both β-arrestin-1 and β-arrestin-2 fused at the N- or C-terminus with the V5-tag; the ALFA-tag was also included as a reference because the corresponding NbALFA intrabody is already characterized and was shown to work well with all placements (N-term, C-term, and internal) of the tag. As shown in Fig.4b-d , all configurations produced a robust signal, but C-terminally tagged NbV5 (NbV5-GFP2) gave a better BRET 2 ratio, while the NbALFA is less affected. As shown in Ext.…”
Section: Resultsmentioning
confidence: 84%
“…Conventional antibodies have proven to be robust workhorses in various cell biology research fields 1 . Notwithstanding their indispensability, their large size and complex architecture preclude them from functioning within living cells 2 . These limitations spurred advances in engineering novel recombinant antibody constructs, termed intracellular antibodies or intrabodies.…”
Section: Introductionmentioning
confidence: 99%
“…We reasoned that nanobody aggregation or misfolding upon intracellular expression ( 32 ) could explain the observed autoactivity (Fig. 1C and fig.…”
Section: Pikobodies Are Functional Nlr-nanobody Fusionsmentioning
confidence: 99%
“…S1). We introduced previously described stabilizing nanobody mutations ( 32 ) in LaG-24, LaM-2, LaM-3, and LaM-6 and found that they abolished Pikobody autoactivity (fig. S2).…”
Section: Pikobodies Are Functional Nlr-nanobody Fusionsmentioning
confidence: 99%
See 1 more Smart Citation